2019
DOI: 10.1001/jama.2019.1432
|View full text |Cite
|
Sign up to set email alerts
|

Association of Midlife Diet With Subsequent Risk for Dementia

Abstract: Importance Observational studies suggest that diet is linked to cognitive health. However, the duration of follow-up in many studies is not sufficient to take into account the long preclinical phase of dementia and the evidence from intervention studies is not conclusive. Objectives To examine whether midlife diet is associated with subsequent risk of dementia. Design, Setting and Participants Population-based cohort study established in 1985-1888, with dietary intake assessment in 1991-1993, 1997-1999 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 40 publications
(91 reference statements)
5
69
1
Order By: Relevance
“…These results are in line with population-based studies, which observed a positive association between adherence to the Mediterranean diet [43][44][45][46], or MIND diet and cognitive decline or dementia [15,16,18,20]. While not all cross-sectional [21,22] and longitudinal [47][48][49] studies did replicate these findings, a meta-analysis on the Mediterranean diet and a systematic review of the MIND diet 50,51]. Extending the evidence from these population-based studies, we here show that higher adherence to the Mediterranean diet and MIND diet are also associated with cognitive outcomes in a sample enriched with subjects who are either clinically or genetically at increased risk for AD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in line with population-based studies, which observed a positive association between adherence to the Mediterranean diet [43][44][45][46], or MIND diet and cognitive decline or dementia [15,16,18,20]. While not all cross-sectional [21,22] and longitudinal [47][48][49] studies did replicate these findings, a meta-analysis on the Mediterranean diet and a systematic review of the MIND diet 50,51]. Extending the evidence from these population-based studies, we here show that higher adherence to the Mediterranean diet and MIND diet are also associated with cognitive outcomes in a sample enriched with subjects who are either clinically or genetically at increased risk for AD.…”
Section: Discussionsupporting
confidence: 89%
“…The relationships between greater adherence to these diets and better cognition, slower cognitive decline and decreased risk for dementia could not always be replicated (e.g., e.g., [20][21][22]). Methodological challenges such as the sensitivity of outcome measures, the most sensitive time periods in life course and the true adherence of cultural diverse populations to the predefined diets might have contributed to these inconsistent findings [23].…”
Section: Introductionmentioning
confidence: 99%
“…A further prospective cohort study with three midlife dietary assessments in 8255 people, followed up for a mean of nearly 25 years, found neither healthy dietary pattern nor Mediterranean diet protected from dementia, except in those with cardiovascular disease, suggesting that diet might influence dementia risk by protecting from the excess risk of cardiovascular risk factors. 147 …”
Section: Specific Potentially Modifiable Risk Factors For Dementiamentioning
confidence: 99%
“…However, there are also research studies which disagree with these positive impacts. They claim that dietary interventions, especially dietary monotherapies, do not have any effect on the improvement of cognitive functions among healthy older population groups (Krause and Roupas, 2017;Akbaraly et al, 2019). But one thing is certain, the dietary approaches are non-invasive and have fewer or no side effects if compared to drug therapies (Klimova and Kuca, 2018).…”
Section: Introductionmentioning
confidence: 99%